Hotel-type nursing and ethical dilemmas due to business interests (Journal of Health Sciences, 2015)
Introduction: In the age of neoliberalism, there are differences in the implementation of nursing activities due to business interests being integrated into nurse-patient relationships. An example of this is hotel-type nursing, which involves fulfilling patients’ needs by charging for nursing services (or by charging an additional fee for extra services). Whether this constitutes a contemporary nursing development or a danger is an important question.  This paper explores an approach to resolving ethical dilemmas, which often emerge when the interests of businesses, nurses, and patients are integrated, as contemporary nursing is implemented according to community care principles.Methods: In a case study of nurses’ activities conducted in June 2013 and 2014 in three different institutions, the methods of observation and interviews were used. The collected data were analyzed using Strengths, Weaknesses, Opportunities, and Threats (SWOT) methodology, and then verified and updated with a power diagram qualitative interpretation and the Decide, Establish, Consider, Identify, Develop, and Implement (DECIDE) decision-making model.Results: Based on my study of hotel-type nursing, an approach to resolving ethical dilemmas which arise with the integration of business interests into nurse-patient relationships is explained.Discussion: Hotel-type nursing involves an adaptation by nurses to a change in their relationship with the patient. This adaptation must ensure that the nurse’s professionalism is recognized as being significantly more beneficial to the patient than a reduction of the nurse’s role to one of simply fulfilling a patient’s wishes.Conclusion: Hotel-type nursing can be advantageous in the development of contemporary nursing if nurses adhere to high ethical standards and practice self-control.